An assessment of knowledge transfer practices for Malaysian construction firm - Zaidi, Mohd Azian; Baharuddin, Mohd Nurfaisal; Bahardin, Nur Fadhilah; Mat Yasin, Mohd Fadzil; Hamid, Md Yusof; Mohd Nawi, Mohd Nasrun (2016)
The aims of this paper are to identify the main factors driving or hindering knowledge transfer practice in the Malaysian construction firm.With extensive knowledge transfer theoretical perspective guides, 17 factors are identified as the key variables that influence construction firm performance for knowledge transfer effectiveness. A mixed methodology approach was employed with qualitative data collected through semi-structured interviews and quantitative data collected through questionnaire survey of the Malaysian contractors. A survey among 151 respondents including a different contractor registration grade was employed for the study.The survey shows that a 17 factors known as creating shared awareness for information sharing, communication, personal skills, individual attitude, training, organizational culture, information technology, motivation, monitoring and supervision, service quality, information accessibility, information supply, socialization process, knowledge tools, coaching and monitoring, staff briefing and information sharing were identify as a key dimension for knowledge transfer success. This finding suggest that through improvement of each factor, the recognition of the whole strategic knowledge transfer process can be increase thus helping to strengthen the Malaysian construction organization for competitive advantages.